2022
DOI: 10.3390/antiox11061179
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Emodin on Oxidized Fish Oil-Induced Metabolic Disorder and Oxidative Stress through Notch-Nrf2 Crosstalk in the Liver of Teleost Megalobrama amblycephala

Abstract: Dietary oxidized lipids are key perpetrator to accumulate excessive reactive oxygen species (ROS) that induce oxidative stress for animals. Immoderate oxidative stress dysregulates cell fate, perturbs cellular homeostasis, thereby interrupts metabolism and normal growth. Therefore, a 12-week feeding trial with fish oil (FO, control group), oxidized fish oil (OF), and emodin-supplemented (OF+E) diets was conducted to evaluate the therapeutic mechanism of emodin on metabolic and oxidative resistance in Megalobra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…26 Besides, emodin mitigates cisplatin-induced augmentation of ROS and oxidative stress in osteosarcoma MG63 cells through activation of the Nrf2/antioxidant response element signaling pathway. 27 In a previous study by Song et al, 28 data suggested that emodin inhibited oxidized fish oil-induced ROS generation in the liver of teleost Megalobrama amblycephala . Moreover, emodin reduced mitochondrial-dependent apoptosis, repressed mitochondrial ROS generation, and accelerated adenosine triphosphate recovery both in a mouse model of renal ischemia/reperfusion injury and in a cellular model of hypoxia/reoxygenation injury.…”
Section: Discussionmentioning
confidence: 92%
“…26 Besides, emodin mitigates cisplatin-induced augmentation of ROS and oxidative stress in osteosarcoma MG63 cells through activation of the Nrf2/antioxidant response element signaling pathway. 27 In a previous study by Song et al, 28 data suggested that emodin inhibited oxidized fish oil-induced ROS generation in the liver of teleost Megalobrama amblycephala . Moreover, emodin reduced mitochondrial-dependent apoptosis, repressed mitochondrial ROS generation, and accelerated adenosine triphosphate recovery both in a mouse model of renal ischemia/reperfusion injury and in a cellular model of hypoxia/reoxygenation injury.…”
Section: Discussionmentioning
confidence: 92%
“…Compared to skin, gill, and muscle tissues, the liver and intestine exhibited a more cumulative response to microplastics, indicating an increase in stress responses with prolonged exposure time. However, with prolonged exposure to negative stimuli, the homeostasis in the fish body may become imbalanced [ 64 ], and the stress-related indicators may cease to increase [ 65 ]. In our study, the values of indicators such as ACP in the liver and AKP in the intestine began to decrease on the fifth day after exposure to microplastics.…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 protects cells from H 2 O 2 , regulating oxidative stress to enable normal cellular function (Hartl et al, 2011). Organisms activate antioxidant defense systems primarily to eliminate toxic substances such as ROS to overcome cellular damage caused by oxidative stress (Song et al, 2022). Representative antioxidant enzymes operating in this context include superoxide dismutase (SOD) and catalase (CAT).…”
Section: Introductionmentioning
confidence: 99%